ANALISIS MANAJEMEN RISIKO TERHDAP DIGITALISASI BISNIS PONDOK PESANTREN - Ahmadi; Nur Aini; Faiz Zainuddin; Syarifuddin (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
Risk management is an integral element of good management and decision-making at every level of an organization. Risk management focuses on decision-making that contributes to the achievement of organizational goals. The purpose of this study is to explain how digitalization-based business practices are implemented at the Nurul Amanah Islamic Boarding School in Bangkalan and how risk management is implemented in business at the Nurul Amanah Islamic Boarding School in Bangkalan. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study explain that (1) The practice of using digital business at the Nurul Amanah Islamic Boarding School is applied to several types of businesses, namely: the Nura Mart business, laundry and canteen. In addition, the application of this digital system applies not only to the business sector, but also operates in the education system that is reported to the guardians of students. (2) Risk management analysis in the use of digital systems at the Nurul Amanah Islamic Boarding School has implemented four systematic provisions, namely risk identification, risk measurement, risk monitoring, and risk control, although not all indicators in the four components are implemented.